PERANAN KANTOR PERTANAHAN KOTA BENGKULU SEBAGAI MEDIATOR DALAM PENYELESAIAN SENGKETA TANAH - Hendi Sastra Putra; Sinung Mufti Hangabei; Mikho Ardinata; Ahmad Dasan (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2022)
Abstract: The increasing demand for land also increases land issues that need to be addressed immediately. Land dispute is a land dispute between individuals, legal entities or institutions that does not have far-reaching implications. Typology of land disputes handled by the Department of ATR / BPN are grouped into: (1) land ownership and property; (2) establishment of land rights and registration; (3) boundary / location of parcels; (4) land acquisition; (5) subject of land reform; (6) Claims for damages for private property; (7) Ulayat Land; (8) Implementation of court decisions. Dispute resolution through consultation and consensus that ends in peace is always better than through court or arbitration. The problem under investigation is the role of the Bengkulu Land Office as a mediator in settling land disputes in Bengkulu City. What are the obstacles in the settlement of land disputes in the city carried out by the Bengkulu City Land Bureau. Empirical legal research is a legal research method that uses empirical facts from human behavior, both verbal behaviors obtained from interviews and real behavior carried out through direct observationKeywords: Country; Dispute; Mediation.